Decision Making Analysis of E-commerce on Generation Z using Analytical Hierarchy Process (AHP) Method - Kaleb Kokoh I Putra; Lisa Carolina; Sarah Devi; Sanny Lim (International Journal of Organizational Business Excellence, 2021)
The research aims to examine what e-commerce platform Generation Z chooses using Analytical Hierarchy Process (AHP) method. Based on a previous exploratory study, there are four criteria that Generation Z pays attention to when choosing an e-commerce platform: ease of use, promotion, product variety, and security. The data was gathered from 250 respondents by using online questionnaires and then analyzed using Expert Choice Software. The research reveals that Generation Z is very concerned about the security aspect of e-commerce platforms. The following criteria are promotion, product variety, and ease of use. It is found that Shopee is the first choice of Generation Z based on the four criteria, followed by Tokopedia, Lazada, and Blibli.